Ant colony optimization for the topological design of interior permanent magnet (IPM) machines. Issue 3 (2014) - ,; ,; ,; ,; ,; ,
Abstract : Purpose – The purpose of this paper is to apply an Ant colony optimization approach for the solution of the topological design of interior permanent magnet (IPM) machines.Design/methodology/approach – The IPM motor design domain is discretized into a suitable equivalent graph representation and an Ant System (AS) algorithm is employed to achieve an efficient distribution of materials into this graph.Findings – The single‐objective problems associated with the maximization of the torque and with the maximization of the shape smoothness of the IPM are investigated. The rotor of the device is discretized into a 9×18 grid in both cases, and three different materials are considered: air, iron and permanent magnet.Research limitations/implications – The graph representation used enables the solution of topological design problems with an arbitrary number of materials, which is relevant for 2 and 3D problems.Originality/value – From the numerical experiments, the AS algorithm was able to achieve reasonable shapes and torque values for both design problems. The results show the relevance of the mechanism for multi‐domain topology optimization of electromagnetic devices. Acknowledgements : This work was supported by the Foreign Affairs and International Trade DFAIT, Canada, and by the following Brazilian agencies: State of Minas Gerais Research Foundation: FAPEMIG (Grants Pronex: TEC 01075/09, Pronem: 04611/10); Coordination for the Improvement of Higher Level Personnel: CAPES; National Council of Scientific and Technologic Development: CNPq (Grants 306910/2006‐3, 141819/2009‐0, 475763/2012‐2, 30506/2010‐2) CNPq Grant no. 472769/2013‐8.